Assessment of Toxic Heavy Metals in Surface Water of the Meghna River Estuary: An Integrated Statistical Approach (The Dhaka University Journal of Earth and Environmental Sciences, 2022)
Rapid industrial development and negligible waste disposal management are considered the driving factors for the major environmental crisis in developing countries like Bangladesh. In the present study, the surface water of Meghna River estuary was evaluated for the concentrations of five toxic heavy metals, namely chromium (Cr), lead (Pb), cadmium (Cd), arsenic (As), and mercury (Hg). All the heavy metals in question were found to be higher than the background value of natural surface water. The toxic heavy metals were in the descending order of Pb>Cr>Hg>Cd>As in the collected water samples. Pb and Hg were found to exceed the lowest biological chronic safety concentration limits recommended by the National Oceanographic and Atmospheric Administration (NOAA), whereas Cr, Cd, and As were under the admissible limits. Principal Component Analysis (PCA), Hierarchical Cluster Analysis (HCA), and Pearson’s correlation analysis suggested that the sources and distribution of those toxic heavy metals are similar. Anthropogenic activities such as industrial waste, agricultural runoff, and municipal solid waste disposal may be responsible for the increased concentration of those metals. Compared to China’s secondary seawater quality standard, the concentration of heavy metals in the Meghna estuary is considerably higher, except arsenic. When compared with previous studies, the heavy metals concentration in the Meghna estuary is significantly higher, which is alarming. From this integrated study, the Meghna estuary is under threatening conditions from ecological and human health perspectives. Further studies are required for temporal monitoring and assessment of the Meghna River estuary.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 10(3), Special Issue 2022: 143-155